COVID-19 Repercussions: Office and Residential Emissions in Pakistan - Rehmani, Mahmood; Arshad, Madiha; Khokhar, Munnawar Naz; Anwer, Naveed; Adnan, Mohammad; Naveed, Rana Tahir; Irshad, Huda (Frontiers in Psychology, 2022)
The purpose of this study is to find empirical evidence on whether work from home or residential emissions reduces office emissions. Based on existing research the study is supported that short-run effects of office emissions i.e., carbon emissions do not outshine the long-run effects. The shift from offices to working from home due to COVID-19 SOPs meant more people operating from home as maintaining their position in the market was crucial. The potential research area is to understand how this would affect energy usage and carbon emissions. This study has used a before and after mixed approach to collect data from 301 working from home employees and 348 top managers responsible for monitoring the employees in work from home setting. Convenience sampling helped timely collect responses as offices were not allowing visitors and collecting data in person was difficult so online surveys were conducted. Work from home reduced usage of office equipment, transportation, pollution etc. The air quality improved considerably but our findings show that the low emissions were only short-lived. This was not a long run scenario as organizations kept practising their operations even at home and the emissions stayed in the environment. Future suggestions and implications are also provided. The results give new insights to researchers in the field of sustainability and the environment.